A meshed kinematical approach for 3D slope stability analysis. (3rd August 2022) - Li, Tianzheng; Gong, Wenping; Tang, Huiming; Zhang, Limin
Abstract: The limit analysis method has been extensively recognized as an efficient tool for a quick estimate of slope stability. Its common practice is to divide the potential failure domain into one or more standard geometric shapes such as the slice method or horn failure mechanism. However, these methods are difficult to solve the problems with spatially varying soil properties, especially for the variation of soil internal friction angles. To solve this problem, a meshed kinematical approach is proposed in this study for 3D slope stability analysis. The proposed approach takes advantage of the spatial discretization technique to achieve the failure mechanism generation based on soil properties rather than a predetermined geometric shape. It also shares some boundary conditions with the well‐known horn failure mechanism to respect the theoretical framework of limit analysis. The obtained failure mechanism is meshed and composed of a large number of well‐arranged elements, which in turn gives it great flexibility and compatibility in integrating spatially discretized data or combining numerical simulation methods. For verification purposes, the proposed approach is tested by some hypothetical slope stability cases and compared with the horn failure mechanism. Two case studies, respectively, involving a multi‐layer slope and a slope subjected to pore water pressure, are presented to illustrate the practical application of the proposed approach. It is concluded that the meshed kinematical approach is effective for slope stability assessment, which can gain high computation accuracy with much less time consumption compared to the numerical simulations.